Faktor-Faktor Yang Mempengaruhi Kinerja Perusahaan Manufaktur Sektor Aneka Industri - Ayu Nurafni Octavia; Ahmad Sahri Romadon; Naini Rizka Amalia (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
This research aims to determine the effect of leverage, liquidity and company size on company performance. The research uses a secondary quantitative data approach, the research population is Manufacturing Companies in the Various Industrial Sectors Registered on the IDX in 2018-2022, samples taken using the purposive sampling method. The data analysis used is multiple linear regression analysis which includes classical assumption tests, hypothesis testing and determination tests. The results of this research show that leverage has no effect on company performance, liquidity has no effect on company performance, company size has a significant positive effect on the performance of manufacturing companies in various industrial sectors listed on the IDX. Simultaneous testing shows that leverage, liquidity and company size jointly influence the company's performance. The coefficient of determination test shows that leverage, liquidity and company size simultaneously influence company performance by 3.9%. Meanwhile, the remaining 96.1% was influenced by other variables not examined in this research